Quality Assessment of DEMs Derived from 1:100,000 Scale Topographic Maps (University of Khartoum Engineering Journal, 2022)
This paper presents the output of a research work undertaken to assess the quality of digital elevation models (DEMs) derived from the 1:100,000 scale topographic maps produced by the Sudan National Survey Department and British Ordnance Survey in 1970’s/ 1980’s. Despite the increasing concern for understanding andworking with errors existing in DEMs, knowledge about DEM quality is still at an early stage, especially in the developing countries. This paper presents the results of the accuracy tests which were performed for different types of topography. The overall TOPOMAP-DEM RMSE was found to be about ±7.066 m. A key outcome of this research is a mathematical model for TOPOMAP-DEM contours quality assessment and a defined procedure for producing a comprehensive DEM quality report. Also it provides the knowledge and the means for incorporating considerations of DEM quality. Additionally, it revealed the possibility of producing DEMs from topographic maps, with reasonable accuracy, using appropriate and unsophisticated interpolation methods such as the natural neighbour (NN) interpolator.